BIRD SPECIES IN TROPICAL FOREST FRAGMENTS, AT DIFFERENT ALTITUDES, IN THE WESTERN ANDES OF ECUADOR (Nativa, 2025)
In this research, the richness, diversity and similarity of bird species were evaluated in six fragments of tropical forests from 170 to 2100 meters above sea level in the western Andes, central Ecuador. The bird count was carried out in 2019 using the technique of counting birds by points, in the forest fragments: Las Cascadas, Ñungañan, Jardín de los Sueños, Los Laureles, Machay, and La Esperanza. The ecological parameters were evaluated by the Shannon Index, relative abundance, and Sorensen Index. The difference between forest fragments and ecological parameters was analyzed using the non-parametric statistical technique of Kruskal-Wallis (p